Brown Shoe: The Guidance of a Footnote - William F. Rogers; Sanford M. Litvack (Washington University Law Quarterly, 1963)
The Brown Shoe decision clarifies two important areas previously undefined. First, for the purpose of measuring the probable horizontal effects of a merger of two competing retailers, a city, including its immediate contiguous surrounding area, exceeding 10,000 in population was held to be a “section of the country” within the meaning of section 7. Second, and of equal significance, was the Court's proscriptions against vertical acquisitions if the acquired company occupies the position of a potential customer of the acquiring company, particularly when, as in Brown, this is coupled with (1) a history of no previous sales to the acquired company in the product market or submarket involved and (2) an evidenced intention to conduct such sales. However, for future guidance in section 7 cases perhaps the most significant aspect of the decision is suggested by footnote 65 and the language of the opinion immediately preceding the footnote.